The Middle East : the cradle of civilization revealed - Bourke, Stephen (Lane Cove, New South Wales : Global Book Publishing, 2008)
Here is an authoritative, detailed and accessible view of the history and peoples' of the ancient Middle East. It is divided into six easily navigable parts arranged chronologically, and then into chapters exploring the history, religion, political and social organization, art, science, and architecture of the peoples' of the region. The text is illustrated with detailed maps and photographs, enabling readers to visualize the ancient places and peoples described, making it the perfect home reference and study aid, as well as a good read for the interested layman.
Introducing the Middle East -- What is the Middle East? -- Peoples and cultures -- Economy and agriculture -- The importance of water -- Archaeological finds -- The fertile crescent : birthplace of agriculture -- Early humans in the Middle East -- The advent of agriculture -- Neolithic cultures -- Mesopotamia : the cradle of civilization -- An urban explosion -- The emergence of city-states -- The city of Ur -- Power struggles : kingdoms at war -- The growth of city-states -- The western states -- The rise of Assyria -- Masters of the known world : the age of empires -- Assyria and its rivals -- Medes and Babylonians -- The Persians -- Under occupation : Hellenistic and Roman conquerors -- Hellenistic conquerors -- Romans and Parthians -- Byzantines and Sasanians -- Search for origins : the rediscovery of the Middle East -- Travelers to an antique land -- The first discoveries -- Developing a discipline.
"Ancient Civilizations" -- at head of t.p.
Includes index and bibliography.
Keywords: Ethnology -- Middle East; Civilization, Assyro-Babylonian.; Sumerians; Babylonia; Babylonia; Middle East -- History -- To 622.; Middle East -- Civilization -- To 622.